Pengelolaan Usaha Tambak Ikan dan Kesesuaiannya terhadap Hukum Islam: Meninjau Pelaksanaan Akad Mudarabah - Husni, Hasmiah; Rusdi, M. Ali; Mutmainnah, Iin (Sekolah Tinggi Agama islam Negeri Majene, 2024)
The sense of help and trust between each other is very high because of the practice of cooperation agreement of fishponds in Ading Village and this practice has long been done. The purpose of the research is to analyse the implementation of fish pond business cooperation and its review according to Islamic law. The object of this research is Ading Village, Wajo Regency. This research is qualitative with an empirical normative approach to solve the problems raised and reviewed with data collection techniques namely observation, interviews, and documentation. The results of this study show that the implementation of cooperation is carried out using a muḍārabah contract where the capital comes from the landowner. However, the implementation is in the form of oral statements without witnesses and the profit-sharing system depends on the initial agreement. This is potentially an element of fraud committed by the investor by taking large quantities of fish and even selling them himself. As for the coverage of losses, it is contrary to Islamic law, because all forms of events in the concept of muḍārabah must be borne by one party, namely the investor, while the manager does not bear losses except for his efforts and work.